Knowledge and civilisation in Islam - Sulaiman, Kabuye Uthman (International Institute of Islamic Thought East and South East Asia & International Islamic University Malaysia, 2017)
THIS is a multi-authored book aimed at undergraduate students. It exposes them to the concepts of knowledge and civilisation in Islam.The authors are PhD holders in Islamic studies and teach at the Department of Fundamental and Inter Disciplinary Studies, Kulliyyah of lslamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia. The aims of this book are threefold. Firstly, to describe the Islamic conception of knowledge with reference to its meaning, classification, aims and importance, the fundamental differences between the Islamic and secular conceptions of knowledge, ethical axioms of learning in Islam with special reference to Abu al-Hasan al-Mawardi's adab al- 'ilm and the Qur'an, true report and the cause of knowledge in the Islamic intellectual tradition. Secondly, to elucidate the concept of civilisation in relation to its meaning, history, common characteristics and importance, Islamic perspective of civilization, the contribution of Muslims to knowledge and civilization, the mosque as a symbol of Islamic civilization, the factors for the rise of the Islamic civilization, the contribution of Muslim scholars to the Islamic civilisation and Islam as the future civilisation of mankind.